OPTICAL PART OF THE EYE AND RELATED DISEASES. - Eshonov Ravshanbek; Kholdarova Gavxaroy Jaliljon's Qizi (Scholar Express Journals, 2023)
Information about the anatomical structure of the eye and its physiology and eye-related diseases and factors in the modern world quoted.
Keywords: receptor; accommodation; sclera; retina